The use of new pedagogical Technologies on the topic of the political map of the world of socio-economic geography lessons (Texas Journal of Multidisciplinary Studies, 2022)
It is known that the organization of classes in interactive methods plays an important role in the development of such features as the memorization of information in students and young people, thinking, taking their position in relation to what is happening around them, and the effective use of the internet. This article will talk about the use of new pedagogical Tehnologies on the topic of the political map of the world of socio-economic geography lessons.